The Effect of Mimicry and Memorisation Method on Mufradât Mastery: A Pre-Experimental Design - Suleman, Zihan; Rawandhy N. Hula, Ibnu; Damhuri; Abdullah (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2024)
The low mastery of students' mufradât is still problematic in learning Arabic in Madrasah. Therefore, it is necessary to apply learning methods to significantly improve students' mastery of mufradât. This study aims to measure the effect of applying the Mimicry and Memorization method on students' mastery of mufradât. This research uses a quantitative experimental method with a pre-experimental design and intact-group comparison form. The study population totaled 30 students and consisted of experimental and control groups. The entire sample was sampled using the purposive sampling technique. Data were analyzed using four techniques: (1) Descriptive Statistical Analysis, (2) Normality Test, (3) Homogeneity Test, and (4) Hypothesis Test. The results showed that the average pre-test score of the experimental group was 18.33, and the post-test score was 71.33. Meanwhile, the average pre-test score of the control group was 28.67, and the post-test score was 57.33. Hypothesis testing using the Mann-Whitney test resulted in an Asymp.Sig. (2-tailed) value of 0.016 <0.05 means Ho is rejected and Ha is accepted. This study concludes that applying the Mimicry and Memorization method affects the mastery of mufradât of class VIII students of MTs N 1 Gorontalo Regency. Rendahnya penguasaan mufradât siswa masih menjadi masalah dalam pembelajaran bahasa Arab di Madrasah. Oleh karena itu, perlu diterapkan metode pembelajaran yang dapat meningkatkan penguasaan mufradât siswa secara signifikan. Penelitian ini bertujuan untuk mengukur pengaruh penerapan metode Mimicry and Memorization terhadap penguasaan mufradât siswa. Penelitian ini menggunakan metode kuantitatif eksperimen dengan desain pre-experimental dan bentuk intact-Group Comparison. Populasi penelitian berjumlah 30 siswa yang terdiri dari kelompok eksperimen dan kelompok kontrol. Seluruh sampel dijadikan sampel dengan menggunakan teknik purposive sampling. Data dianalisis menggunakan empat teknik (1) Analisis Statistik Deskriptif (2) Uji Normalitas, (3) Uji Homogenitas, dan (4) Uji Hipotesis. Hasil penelitian menunjukkan bahwa rata-rata nilai pre-test kelompok eksperimen adalah 18,33 dan nilai post-test adalah 71,33. Sementara itu, rata-rata nilai pre-test kelompok kontrol adalah 28,67 dan nilai post-test adalah 57,33. Uji hipotesis menggunakan uji Mann-Whitney menghasilkan nilai Asymp.Sig.(2-tiled) 0,016 < 0,05, yang berarti Ho ditolak dan Ha diterima. Simpulan penelitian ini bahwa penerapan metode Mimicry and Memorization berpengaruh terhadap penguasaan mufradât siswa kelas VIII MTs N 1 Kabupaten Gorontalo.